The Long Civil War: New Explorations of America’s Enduring Conflict - Smith, John David; Arsenault, Raymond (New Directions in Southern History, 2021)
In this wide-ranging volume , eminent historians John David Smith and Raymond Arsenault assemble a distinguished group of scholars to build on the growing body of work on the "Long Civil War" and break new ground.